Absence of PSA Flare With Apalutamide Administered 1 Hour in Advance With GnRH Agonists: Case Report - Hu, Zhiquan; Liu, Zhenghao; Chen, Zhiyuan; Zeng, Xing; Wang, Zhihua; Yang, Chunguang (Frontiers in Oncology, 2022)
Objective To examine the effects of apalutamide on endocrine function and flare prevention in metastatic hormone-sensitive prostate cancer (mHSPC) patients administered GnRH agonists. Methods The first newly diagnosed mHSPC patient took apalutamide for 2 weeks followed by combination with GnRH agonist, as recommended by clinical guidelines. Serum luteinizing hormone (LH), testosterone, and PSA were detected during the oral administration of apalutamide before and after ADT. Eight newly diagnosed mHSPC patients innovatively took apalutamide 1 hour before GnRH agonist administration; LH, testosterone and PSA were detected before and after ADT. Results In the first patient, LH and testosterone levels were increased during apalutamide monotherapy, and serum PSA levels decreased rapidly, demonstrating apalutamide effectively blocked AR signaling. In patients on the 1-hour regimen, combined treatment with apalutamide and GnRH agonists led to peak level of testosterone on day 3 and castration level on day 28, while PSA decreased continuously. No one experienced dysuria or bone pain worsen after ADT. Conclusion Taking apalutamide 1 hour in advance may effectively prevent the flare-up effect in prostate cancer patients treated with GnRH agonists. Compared with the 2-week regimen, the 1-hour regimen could simplify the treatment process and bring testosterone to castration levels in advance.